Sosialiasi Dan Upaya Pencegahan Banjir Dengan Penanaman Pohon Alpukat Guna Mencegah Bahaya Erosi - Devina Chandra; Manuppak Irianto Tampubolon; Dumartina Hutauruk (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Flooding is one of the natural disasters that occurred from the beginning of 2000 until now during the rainy season. This problem must be overcome with knowledge and a sense of community awareness in understanding disaster mitigation, especially floods, which is the aim of implementing this community service. This community service method involves lectures and tree planting, followed by data analysis for community understanding using descriptive qualitative methods. Based on the evaluation results, it shows that there has been an increase in public understanding about disaster mitigation.